2019
DOI: 10.1002/slct.201803538
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed One‐Pot Synthesis of Pyrrolo[1,2‐a]quinoxaline Derivatives from 1‐(2‐Aminophenyl)‐pyrroles and Aldehydes

Abstract: A facile and highly efficient copper-catalyzed strategy has been developed for the synthesis of pyrrolo[1,2-a]quinoxalines from 1-(2-aminophenyl)-pyrroles and aldehydes at room temperature. This reaction proceeds via imine formation, cyclisation, and oxidation in one-pot. This strategy provides a facile and rapid access to pyrrolo[1,2-a]quinoxalines in good to high yields under mild conditions. This process has several advantages, such as simple reaction procedure, readily available starting materials, low cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…At present, C4-substituted pyrrolo/indolo­[1,2- a ]­quinoxalines are actively involved in various biomedicinal applications such as central 5-HT 3 receptor antagonists, D-loop activity of RAD51 inhibitors, antileishmanial, antimalarial, anticancer, and anti-HIV activities. Usually, a two-component condensation or oxidative cyclization reaction of N -(2-aminophenyl)­pyrroles/indoles and a variety of carbonyl equivalents including aromatic aldehydes, aryl ketones, aryl acetic acids, pinacols, α-amino acids, benzyl amines, benzyl halides, styrenes, phenylacetylenes, dimethyl sulfoxide, α-carbonyl sulfonium ylide, and alkylboronic acids efficaciously constructs various C4-substituted pyrrolo/indolo­[1,2- a ]­quinoxalines. In 2015, Chen Ma et al reported p -TsOH-catalyzed unusual C–C bond cleavage of 1,3-diketones and β-keto esters to produce a series of 4-aryl/alkylpyrrolo/indolo­[1,2- a ]­quinoxalines (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…At present, C4-substituted pyrrolo/indolo­[1,2- a ]­quinoxalines are actively involved in various biomedicinal applications such as central 5-HT 3 receptor antagonists, D-loop activity of RAD51 inhibitors, antileishmanial, antimalarial, anticancer, and anti-HIV activities. Usually, a two-component condensation or oxidative cyclization reaction of N -(2-aminophenyl)­pyrroles/indoles and a variety of carbonyl equivalents including aromatic aldehydes, aryl ketones, aryl acetic acids, pinacols, α-amino acids, benzyl amines, benzyl halides, styrenes, phenylacetylenes, dimethyl sulfoxide, α-carbonyl sulfonium ylide, and alkylboronic acids efficaciously constructs various C4-substituted pyrrolo/indolo­[1,2- a ]­quinoxalines. In 2015, Chen Ma et al reported p -TsOH-catalyzed unusual C–C bond cleavage of 1,3-diketones and β-keto esters to produce a series of 4-aryl/alkylpyrrolo/indolo­[1,2- a ]­quinoxalines (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…19 Recently, Krishna reported a one-pot copper-catalysed synthesis of pyrrolo[1,2-a]quinoxalines from 1-(2-aminophenyl)pyrroles and aldehydes. 20 These multistep syntheses have led to moderate yields and, in most cases, require the use of toxic reagents. Therefore, it is highly desirable to develop an efficient, nontoxic and convenient approach for the synthesis of 4-substituted pyrroloquinoxalines.…”
mentioning
confidence: 99%
“…Infrared spectra were recorded on an Agilent Technologies Cary 630 FT-IR spectrometer.All of the synthesised pyrrolo[1,2-a]quinoxaline derivatives were characterised and are in good agreement with those reported in the literature. [4][5][6][7][8][9][10] The spectral data of the novel pyrrolo[1,2-a]quinoxalines are shown from S11 onwards.…”
mentioning
confidence: 99%